2004
DOI: 10.1021/es0352294
|View full text |Cite
|
Sign up to set email alerts
|

Using Chromium Stable Isotope Ratios To Quantify Cr(VI) Reduction:  Lack of Sorption Effects

Abstract: Chromium stable isotope values can be effectively used to monitor reduction of Cr(VI) in natural waters. We investigate effects of sorption during transport of Cr(VI) which may also shift Cr isotopes values, complicating efforts to quantify reduction. This study shows that Cr stable isotope fractionation caused by sorption is negligible. Equilibrium fractionation of Cr stable isotopes between dissolved Cr(VI) and Cr(VI) adsorbed onto gamma-Al2O3 and goethite is less than 0.04 per thousand (53Cr/52Cr) under env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 26 publications
2
98
0
1
Order By: Relevance
“…In contrast Fe (II) sorbed on goethite particles is isotopically heavy compared to dissolved Fe (II) . For Cr, a negligible isotope fractionation is reported (Ellis et al 2004).…”
Section: 7mentioning
confidence: 99%
“…In contrast Fe (II) sorbed on goethite particles is isotopically heavy compared to dissolved Fe (II) . For Cr, a negligible isotope fractionation is reported (Ellis et al 2004).…”
Section: 7mentioning
confidence: 99%
“…First, the Cr isotope system was used to track the reduction of toxic and soluble Cr(VI) to benign and immobile Cr(III) in groundwater (Ellis et al, 2004. These studies observed the preferential reduction of isotopically light chromate/ CrO 4 2-, which resulted in the remaining Cr(VI) pool becoming isotopically heavier as the reduction proceeded.…”
Section: Research History Of the Cr Isotopic Systemmentioning
confidence: 99%
“…The light Cr isotope ( 52 Cr) is assumed to be preferentially retained with Cr(III) within the weathered soil whereas the oxidized and mobilized Cr(VI) is enriched in the heavy 53 Cr isotope (Izbicki et al, 2008;Crowe et al, 2013;Frei and Polat, 2013;Berger and Frei, 2014) and transported -potentially without significant isotope effect during adsorption onto particles (Ellis et al, 2004) -via river water to the open ocean (Bonnand et al, 2013;Frei et al, 2014;Paulukat et al, 2015). There, oxygenated water stabilizes the transported Cr signal (Table 1); the position of samples presented in this figure correlates to their position in the schematic stratigraphic column and to their deposition on the Yangtze Platform (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During transport to the oceans, Cr(VI) is potentially again partially reduced (Ellis et al, 2002;Sikora et al, 2008;Døssing et al, 2011;Kitchen et al, 2012;Basu et al, 2014), which would result in an additional enrichment of the remaining dissolved Cr(VI) in 53 Cr, whereas 53 Cr-depleted Cr(III) is likely to be precipitated and/or adsorbed (Ellis et al, 2002(Ellis et al, , 2004Crowe et al, 2013). The overall Cr isotope composition of seawater is potentially affected if the influence of the mobile 53 Cr-enriched Cr(VI) input is large enough (Crowe et al, 2013).…”
Section: Oxidative Weathering Indicated By Cr Isotopesmentioning
confidence: 99%
See 1 more Smart Citation